PHEROMONE SYNERGISTS AS CO-ATTRACTANT FOR OLFACTORY TRAPPING OF SCAPANES AUSTRALIS BSDV. (COLEOPTERA: SCARABAEIDAE) PEST OF COCONUT IN PAPUA NEW GUINEA - Titus Kakul; Didier Rochat; Jean Paul Morin; P. Gende; S. Embupa; L. Ollivier (International Coconut Community Journal, 2004)
Olfactory trapping of Scapanes australis is being studied to develop it to complement existing control methods. Components required were traps, pheromone and pheromone synergist. The first two have been developed while field trials carried out to determine an efficient synergist co-attractant is reported. Synthetic synergist mixtures of compounds emitted from fermenting sugarcane were tested in comparison to split stalk of garden grown sugarcane and split bulb of nursery coconut. Some of the mixtures produced synergistic effect similar to sugarcane but lower than split bulb of coconut. Placing live Scapanes adult inside the stalk of sugarcane increased catches similar to the split bulb of coconut. This will enable the formulation of an efficient tool of beetle control.